Pelatihan Pembuatan Hand Sanitizer Serai Berbasis Andragogi di Desa Suco Mumbulsari Jember - Nurotul Wafiroh; Arief Tukiman Hendrawijaya; Muhammad Irfan Hilmi; Lutfi Ariefianto; Utariyati Utariyati (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2026)
This community service article focuses on training adult learners to produce lemongrass-based hand sanitizer in Mandigu Hamlet, Suco Village, Mumbulsari District, Jember Regency. The program was motivated by the need to strengthen hand hygiene during the pandemic and by the availability of lemongrass as a local resource. The objectives were to describe the training process, analyse its achievements and benefits, and interpret it through adult education or andragogical principles. The service method combined service learning and community development through local potential observation, coordination, socialization, demonstration, hands-on production, product labelling, evaluation, and reflection. The results show that the training was implemented as part of a forty-five-day community service program with an 80% implementation achievement. Participants gained practical experience in transforming lemongrass into a functional product, improved their understanding of hand hygiene, and engaged in contextual learning. Andragogical analysis indicates that the training was supported by real learning needs, prior experiences, hands-on practice, accessible communication, and flexible scheduling.